Psychosocial factors impacting on life transitions among young adults with type 2 diabetes: an Australian – Danish qualitative study. Issue 2 (2nd June 2015) - Rasmussen, B.; Terkildsen Maindal, H.; Livingston, P.; Dunning, T.; Lorentzen, V.
Abstract : Background: Type 2 diabetes (T2DM) prevalence is increasing rapidly worldwide with a significant increase in young adults. There is limited information about psychosocial and service needs of this group. Aim: To explore similarities and differences in how psychosocial factors impact on Australian and Danish young adults with T2DM and to identify unmet support needs during life transitions. Method: A qualitative approach was adopted using thematic content analysis of 26 in‐depth semi‐structured interviews. An inductive descriptive content analysis was undertaken using a comparative coding system. Findings: Eligible participants were from Australia (12) and Denmark (14), aged 19–42 years who had T2DM for more than 10 months. In general, they reported diabetes management was difficult during transitions and diabetes self‐care routines had to change to accommodate life changes. The underpinning sense of 'uncertainty' initiated by life transitions caused guilt that often resulted in low self‐worth, anxiety and depression, which in turn had a negative impact on social and professional relationships. The participants emphasised the importance of connectedness to social networks, particularly with T2DM peers, and the need for flexible access to health professionals, age‐specific tailored support and lower costs for Australians. Australian participants were more concerned than Danish participants about the cost associated with diabetes care and their ability to stay employed; hence, they were reluctant to disclose diabetes at work. Conclusion: T2DM had a similar impact on life transitions of Australian and Danish young adults with T2DM, suggesting health care needs to encompass managing life transitions. Participants had to cope with uncertainty and the impact of people's responses to diabetes, particularly at work and in relationships. Health professionals are urged to integrate these factors in care plans and education, which must be individualised and focus on the psychosocial aspects that operate during life transitions.